2017
DOI: 10.1002/cm.21410
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution imaging of muscle attachment structures in Caenorhabditis elegans

Abstract: We used structured illumination microscopy (SIM) to obtain super-resolution images of muscle attachment structures in C. elegans striated muscle. SIM imaging of M-line components revealed two patterns: PAT-3 (β-integrin) and proteins that interact in a complex with the cytoplasmic tail of β-integrin and localize to the basal muscle cell membrane (UNC-112 (kindlin), PAT-4 (ILK), UNC-97 (PINCH), PAT-6 (α-parvin) and UNC-95), are found in discrete, angled segments with gaps. In contrast, proteins localized throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…2 (top row), there is clearly a thin band of F-actin that lies near the muscle cell boundary (indicated by yellow arrow), which can be identified by three criteria: (1) its location between two adjacent spindle-shaped body wall muscle cells (Supplementary Fig. 2 ), (2) being thinner than a typical I-band which alternates with myosin A-bands, and (3) not projecting throughout the depth of the myofilament lattice 5 like a typical I-band, which can be discerned by observing less intense signal when the optical slice is taken deeper into the lattice (the label of deeper part in Fig. 2 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 (top row), there is clearly a thin band of F-actin that lies near the muscle cell boundary (indicated by yellow arrow), which can be identified by three criteria: (1) its location between two adjacent spindle-shaped body wall muscle cells (Supplementary Fig. 2 ), (2) being thinner than a typical I-band which alternates with myosin A-bands, and (3) not projecting throughout the depth of the myofilament lattice 5 like a typical I-band, which can be discerned by observing less intense signal when the optical slice is taken deeper into the lattice (the label of deeper part in Fig. 2 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Closer examination of confocal images of pix-1(gk893650) shows that the boundary defect is more subtle in this mutant than in the nonsense and intragenic deletion pix-1 mutants. In Qadota et al 5 , we reported that by structured illumination microscopy (SIM), in wild-type muscle, the boundaries appear like a zipper, in which the two sides of the zipper are closely apposed to each other (as if the zipper were closed). Zoomed-in confocal views of muscle ( ; sfIs20] in which the muscle cell boundary defect observed in the nonsense mutant pix-1(gk299374) has been rescued by an integrated array of wild-type pix-1 expressed from a muscle-specific promoter (see Fig.…”
Section: Determination Of the Pix-1 Signaling Pathway In Musclementioning
confidence: 97%
See 1 more Smart Citation
“…Unlike vertebrates, the contractile forces in C. elegans are mostly transmitted laterally to the cuticle resulting in bending and sinuous locomotion of the worm on an agar surface (14). In addition, integrin adhesion complexes exist at attachment plaques lying at the boundaries between adjacent muscle cells separated by basement membrane (15), and these also are likely to be involved in force transmission as their absence results in a locomotion defect (16).…”
Section: Introductionmentioning
confidence: 99%
“…The conserved molecular pathways contributing to sarcomere structure, and muscle function have been studied in C. elegans using a variety of methods. The animal's transparent body along with immunostaining approaches and various microscopy techniques has helped to visualize the muscle structure (15,(17)(18)(19)(20)(21). Impairments in muscle function due to genetic defects have been studied by observation of gross phenotypes such as "Unc" (Uncoordinated) adults and "Pat" (Paralyzed arrest at 2-fold) embryonic lethals (13,17,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%